Acrosomal Changes during Liquid Preservation of Boar Semen with BTS, KLEV and BI-1 Dilutors - PANDEY, R P; SINGH, B K (The Indian Journal of Animal Reproduction, 2023)
Changes in acrosome morphology of 12 semen samples diluted with BTS, Kiev and 81-1dilutors and preserved for 0, 24, 48 and 72 hours were evaluated. Highly significant (P < 0.05) effect of both hours of preservation and dilutors was noted on the incidence of damaged _ apical ridge. The percentage of DAR increased significantly at 48 hours of preservation with BTS and Kiev dilutors where as with Bl-1 dilutor it increased earlier at 24 hours of preservation. The incidence of missing special ridge was detected at 48 hours of preservation with BTS and Kiev dilutors. Highly significant effect (P <0.01) of both hours of preservation and dilutors was recorded on incidence of loose acrosomalcap at 24, 48 and 72 hours of preservation.